2020
DOI: 10.1183/13993003.03498-2020
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation and external validation of 22 prognostic models among hospitalised adults with COVID-19: an observational cohort study

Abstract: BackgroundThe number of proposed prognostic models for COVID-19 is growing rapidly, but it is unknown whether any are suitable for widespread clinical implementation.MethodsWe independently externally validated the performance candidate prognostic models, identified through a living systematic review, among consecutive adults admitted to hospital with a final diagnosis of COVID-19. We reconstructed candidate models as per original descriptions and evaluated performance for their original intended outcomes usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
183
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(206 citation statements)
references
References 40 publications
18
183
2
3
Order By: Relevance
“…Similar to other studies, we found that older age is the main risk factor for dying from COVID-19, with every 10-year increase associated with the largest increases in the HR [11,14,23]. In a recent prospective validation study of prognostic models for COVID-19, none of the models that predicted mortality in patients with COVID-19 were better than age alone to predict in-hospital mortality [24]. This may be explained by the fact that many models for COVID-19 have failed to account for the large increases in mortality risk due to increasing ages.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to other studies, we found that older age is the main risk factor for dying from COVID-19, with every 10-year increase associated with the largest increases in the HR [11,14,23]. In a recent prospective validation study of prognostic models for COVID-19, none of the models that predicted mortality in patients with COVID-19 were better than age alone to predict in-hospital mortality [24]. This may be explained by the fact that many models for COVID-19 have failed to account for the large increases in mortality risk due to increasing ages.…”
Section: Discussionsupporting
confidence: 88%
“…We only included participants admitted or first assessed for COVID-19 until 26/08/2020 in order to allow a minimum four-week interval for registration of outcome events (until final data extraction date of 24/09/2020). Participants who had ongoing hospital care at the end of follow-up were classified as not meeting the endpoint, since the risk of deterioration declines with time since admission 8 . Missing outcomes were imputed, as described below.…”
Section: Discussionmentioning
confidence: 99%
“…Decision curve analysis was also done in the internal-external cross-validation validation sets to quantify the net benefit of implementing the model in clinical practice 28 , compared to: (a) a 'treat all' approach; (b) a 'treat none' approach; and (c) using other candidate generic and COVID-specific clinical prognostic models to stratify treatment, identified by recent systematic reviews 6,8,9 . Only candidate models where constituent variables were available among >60% of the cohort were considered.…”
Section: Internal-external Cross-validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus (SARS-CoV-2; a single-stranded RNA virus) poses an unprecedented challenge to health care systems globally. It is increasingly apparent that conventional prognostic scores for critically ill patients admitted to intensive care units (ICUs) such as the APACHE II (Acute Physiology and Chronic Health Evaluation) score 1 and SOFA (Sequential Organ Failure Assessment) score 2 , are not discriminatory in COVID-19 ICU patients [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%